2017
DOI: 10.1080/15226514.2016.1267700
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of soil trace elements by willow during a phytoremediation trial in Southern Québec, Canada

Abstract: The phytoextraction of the trace elements (TEs) As, Cd, Cu, Ni, Pb, and Zn by willow cultivars (Fish Creek, SV1 and SX67) was measured during a 3-year field trial in a mildly contaminated soil. Biomass ranged from 2.8 to 4.4 Mg/ha/year at 30,000 plants/ha. Shoots (62%) were the main component followed by leaves (23%) and roots (15%). Biomass was positively linked to soluble soil dissolved organic carbon, K, and Mg, while TEs, not Cd and Zn, had a negative effect. The TE concentration ranking was: Zn > Cu > Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…Poplar and Salix gave yields not statistically different from each other (at p = 0.05), probably due to water scarcity in the field, as from previous studies in northern Italy with fertilized and irrigated soil, poplars are usually more productive [29,37]. The results were, however, in line with productions made on marginal areas and on contaminated soils [13,17]. In this case, to maximally limit the management of the parcels it was chosen not to irrigate the field unless in the case of extreme drought.…”
Section: Biomass Productionsupporting
confidence: 52%
See 2 more Smart Citations
“…Poplar and Salix gave yields not statistically different from each other (at p = 0.05), probably due to water scarcity in the field, as from previous studies in northern Italy with fertilized and irrigated soil, poplars are usually more productive [29,37]. The results were, however, in line with productions made on marginal areas and on contaminated soils [13,17]. In this case, to maximally limit the management of the parcels it was chosen not to irrigate the field unless in the case of extreme drought.…”
Section: Biomass Productionsupporting
confidence: 52%
“…Generally, productivity was not higher as in the literature [13,29], probably due to low soil fertility or the limited quantity of water. However, as the plant did not present symptoms of suffering, to increase biomass production a higher planting density is attainable, in order to store higher amounts of PTE in plant tissues.…”
Section: Genotypementioning
confidence: 52%
See 1 more Smart Citation
“…There have been many reports since then on the use of some crop plants and forest species (including poplar and willows) to remove Cd from contaminated soils [4,10,25,[37][38][39][40]. It has been reported that a few clones of willows have high heavy metal tolerance [13][14]41].…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of phytoextraction depends on the capacity of the plants to concentrate and accumulate contaminants in their aerial parts. While highly productive species will be more effective for phytoextraction (Kacál-ková et al 2014, Courchesne et al 2017) the actual efficiency of phytoextraction depends primarily on the capacity of plants to establish and survive on contaminated sites (Walter et al 2003). Consequently, it is important to identify plants well adapted to the urban context and capable of supporting abiotic stresses related to these conditions, specifically water and heat stresses, air pollution, etc.…”
Section: Introductionmentioning
confidence: 99%